Análise experimental e numérica da remoção dos herbicidas ácido diclorofenoxiacético (2,4 D) e atrazina de efluentes líquidos - Cocco, Natália Maier (2021)
The present work studies a batch adsorption process for the removal of herbicides that, due to their large consumption on the soil surface of agricultural plantations, have been accumulating and may exceed the limits of their concentration in soil and groundwater. Standing out for their use, dichlorophenoxyacetic acid (2,4 – D) and atrazine are the herbicides studied in this work. Adsorption was the unit operation selected for the removal of herbicides from liquid effluents due to the simplicity of operation and technical feasibility. Most herbicide adsorption studies are focused on the removal of a specific herbicide, but from a practical point of view, an adsorbent material that corresponds to more than one herbicide is needed, so that this occurs more efficiently in the environment. As a promising adsorbent for removing both 2,4D and atrazine, an activated carbon with good special characteristics and special adsorption characteristics was used. Initially, the optimal value of the activated charcoal dosage in the removal of 2,4-D and atrazine herbicides was determined. Then, the study of the kinetic profile, equilibrium behavior and thermodynamic parameters of batch adsorption using activated carbon in aqueous solutions was carried out. Finally, to prove the efficiency of the adsorption system, an evaluation of the removal of the herbicides, dichlorophenoxyacetic acid (2,4 – D) and atrazine, in a real effluent was carried out. The adsorption of herbicides by activated carbon in real effluent was also effective, being the removal percentage being around 84% for 2,4-D and 83% for atrazine, a result that corroborates the potential of the activated carbon under study for removal of herbicides from liquid effluents.